Influence of Radio Coverage of Conditions in Nigerian Correctional Centres on Port Harcourt Residents’ Perception of the Treatment of Inmates by Authorities - Kasarachi Hayford (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study was predicated on the need to analyse the influence of radio coverage of conditions in Nigeria’s correctional centres on how Port Harcourt residents perceive how the authorities treat the inmates in these centres. With Agenda Setting and Selective Influence theories as base, the study formulated four research questions. The sample size for the study was 384 (survey) and 24 (content analysis) drawn from a population size of 756,000 and 24 respectively. Among other findings, the study showed that in terms of pattern, radio stations covered conditions in Nigerian Corrective Centres frequently and prominently in detailed fashion. The results also showed that the residents recorded a high level of listenership to the selected programmes and also had a high rate of encounter of issues relating to the corrective centres. Finally, findings showed that the radio coverage of the correctional centres influences how the residents perceive the treatment of the inmates by the authorities. The study recommended that radio stations in Rivers State should maintain the pattern of coverage of the correctional centres so as to lead to advocacy and generate public discourse leading to reforms in the sector.